Tungsten Langmuir probes from JET-with the ITER-Like Wall: Assessment of mechanical properties by nano-indentation. (8th December 2021) - Spychalski, Maciej; Fortuna-Zalesna, E; Zdunek, Joanna; Rubel, Marek; Widdowson, Anna; Aleiferis, Spyridon; Thomas, Beth
Abstract: Tungsten Langmuir probes retrieved from the JET tokamak with the ITER-Like Wall (JET-ILW) after the second ILW campaign were examined by nano-indentation, microscopy and x-ray diffraction in order to determine changes in mechanical properties and phase composition. Not-exposed probe served as a reference material. Two regions were studied: (i) recrystallized region below the tip and, (ii) the lower probe structure, called 'support structure'. A large difference between the hardness in the tip and the other region has been found: 5 GPa versus 15 GPa, respectively. The measured values of the Young's modulus in both zones of exposed probe are at the same level of 260 GPa. From the force-displacement curves, it can be concluded that the material in the tip has a smaller range of elastic deformations compared to that characteristic for the support structure. The values obtained for the material in its initial state are consistent with the available literature data for tungsten. With x-ray diffraction and microscopy only tungsten has been detected in the probe tip. It remained clean and free from impurities and undesirable compounds, which could have a negative impact on the probes electrical properties.